Expansion in size of a terminal deletion: a paradigm shift for parental follow-up studies. Issue 6 (15th April 2008) - South, S T; Rope, A F; Lamb, A N; Aston, E; Glaus, N; Whitby, H; Maxwell, T; Zhu, X L; Brothman, A R
Abstract : Background: Parental studies are often necessary subsequent to the identification of a chromosome abnormality. The recommended studies are based on assumptions about how chromosome rearrangements occur. One such assumption is that deletion size is stable through generations. Results: We have identified a family where a small subtelomeric deletion in a phenotypically and cytogenetically normal mother expanded nearly 10-fold into a clinically consequential and cytogenetically visible deletion in her affected daughter. Conclusion: Traditional parental follow-up studies would have not identified this expansion, but would have rather classified the deletion in the daughter as either de novo or benign. Only by sizing the deletion by array comparative genomic hybridisation in both the mother and the daughter was the expansion recognised. Previous assumptions about chromosome behaviour suggest that this phenomenon may have been easily missed in other cases of chromosomal deletions. Therefore, this case illustrates the need for more comprehensive analyses of parental chromosome structure when characterising an abnormality in a child.